Small bowel obstruction secondary to an adhesion between ovary and small intestine loops: Case report - Belghali, Houssam; Hamdouni, Younes; Ibn Majdoub, Karim; Toughrai, İmane; Mazaz, Khalid (Journal of Surgery and Medicine, 2019)
Adhesion-related small bowel obstruction is a common pathology in visceral surgery. Postoperative adhesion is the most common etiology of acute intestinal occlusion. We report the case of an intestinal occlusion caused by an adhesion between the ovary and the small bowel loops. In order to share the epidemiological, clinical, prognostic and therapeutic aspects of this affection, and also the unusual localization of the adhesion, this is described in our case report. Computed tomography has improved the diagnosis of adhesive small bowel obstruction and its findings in bowel ischemia are helpful to guide the therapeutic attitude. The treatment was surgical and the postoperative course was simple.